Toxic Positivity di Tempat Kerja: Pengembangan Skala Pengukuran - Sugiyanto Sugiyanto; Risydah Fadilah (Jurnal Psikologi Perseptual, 2026)
Toxic positivity has increasingly drawn attention in modern workplaces, where the culture of always being positive often conceals employees’ emotional vulnerability. This study aims to develop and validate a toxic positivity scale in the Indonesian workplace context. A total of 558 participants were recruited for meeting inclusion criteria. The scale development began with 25 items validated by five psychology experts using the Content Validity Ratio (CVR), leaving 22 items for testing. Exploratory Factor Analysis (EFA) using JASP revealed a single-factor structure with 16 items after controlling for negative wording effects. Confirmatory Factor Analysis (CFA) using SmartPLS 4 confirmed the unidimensional structure with high reliability (α=0.982; AVE=0.690). Multi-Group Analysis (MGA) showed full invariance across gender but only configural and metric invariance across generations. These findings highlight the toxic positivity at work scale as a valid and reliable tool to identify the hidden risks of overly positive organizational cultures on employee well-being. Fenomena toxic positivity semakin menjadi perhatian dalam dunia kerja modern, di mana budaya selalu positif sering menyembunyikan kerentanan emosional pekerja. Penelitian ini bertujuan mengembangkan dan memvalidasi skala toxic positivity dalam konteks organisasi di Indonesia. Sebanyak 578 partisipan diikutsertakan dan memenuhi kriteria. Proses pengembangan skala dimulai dengan 25 butir pernyataan yang divalidasi oleh lima ahli psikologi menggunakan Content Validity Ratio (CVR) menghasilkan 22 item yang layak diuji. Analisis faktor eksploratori (EFA) menggunakan JASP menunjukkan satu faktor utama dengan 16 item setelah mengontrol efek negatif wording. Hasil analisis faktor konfirmatori (CFA) dengan SmartPLS 4 mengonfirmasi struktur unidimensional dengan reliabilitas tinggi (α=0.982; AVE=0.690). Uji Multi-Group Analysis (MGA) menunjukkan invariansi penuh pada gender, tetapi hanya configural dan metric invariance tercapai pada generasi. Temuan ini menegaskan pentingnya skala toxic positivity di tempat kerja untuk mengidentifikasi dampak budaya positif semu terhadap kesejahteraan karyawan.